(untitled) - Lester, Mark (New York, 2013)
Whether your skills need drastic improvement or a quick brush-up, The McGraw-Hill Handbook of English Grammar and Usage will get your grammar back on the right track with: Straightforward explanations of common mistakes and why they happen. Hundreds of correct and incorrect sentence examples, with errors clearly marked. Quick tips for fixing your most stubborn grammatical mishaps. Catchy memory aids for writing correctly the first time.
Keywords: Tiếng Anh,English language; Ngữ pháp,Grammar